Design of pico-hydro turbine by using a pump as a generator - Mohd Akmal, Mat Ludin (2013)
Nowadays, hydropower is one of the significant renewable energy that most developed. This source of energy is hugely known as an environmental friendly operation put it as a main choice among other salvage source of energy. The objective of this project is to design a pico hydro turbine that can generate a sufficient amount of energy by modifying an aquarium pump and turn it into a generator. Besides that, the purpose of this project also to build a useful, effective, convenience, reliable, environment friendly and safe to use turbine. The project scopes were to design, modified, analyze and implement it as a renewable source of energy. Different kinds of blade design were used to aid in gathering information on the efficiency of the turbine. This turbine design is efficient, portable and able to operate in many different kind of flow to generate electricity such as using a wind or in the river. The testing for the turbine was carried out to meet the objective of this project. Result from this study can contribute to the future Research and Development (R&D) particularly in the field of small scale hydropower generation